Microscopic Coulomb interaction in transition-metal dichalcogenides. (19th October 2020) - Neuhaus, J; Liebscher, S C; Meckbach, L; Stroucken, T; Koch, S W
Abstract: The quasi-two dimensional Coulomb interaction potential in transition metal dichalcogenides is determined using the Kohn–Sham wave functions obtained from ab initio calculations. An effective form factor is derived that accounts for the finite extension of the wave functions in the direction perpendicular to the material layer. The resulting Coulomb matrix elements are used in microscopic calculations based on the Dirac Bloch equations yielding an efficient method to calculate the band gap and the opto-electronic material properties in different environments and under various excitation conditions.